Meningkatkan Kemampuan Membaca Sekolah Dasar di UPT SDN.060835 Medan Barat - Weni Sapira Matondang; Gusti Pirandy; Nurbaiti Nurbaiti (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
The teaching campus is a program of the Merdeka Learning Kampus Merdeka (MBKM) created by the Ministry of Education and Culture of the Republic of Indonesia. This program aims to assist the learning process in Elementary Schools (SD) so that they are able to carry out an effective teaching and learning process. Through the teaching campus program, students have the responsibility of assisting teaching and learning activities, assisting the administration of the school where they are assigned. USU's teaching partner campuses are carried out to improve students' abilities, gain experience and to apply what has been previously learned. The author is placed in SD Negeri 060835 jl. Sei deli no. 3 kelurahan Silalas Kec. West Medan. In implementing this program the authors focused on learning to read because many students in the upper grades still could not read. In this program the method used is the method of social work, namely group work. This is done because the author comes from the Department of Social Welfare.